(untitled) (Research, Society and Development, 2022)
Anthocyanins are water-soluble polyphenols responsible for the color of many fruits, flowers, and vegetables. In addition to natural dyes, anthocyanins are also related to the prevention of several chronic diseases. However, anthocyanins are extremely sensitive to variations in pH, temperature, light, enzymes, and other environment variables, being necessary to employ artifices and technologies to expand their application in both the food and pharmaceutical sectors. In this context, biopolymeric nanoparticles can be used to protect and intensify the functions conferred to the anthocyanins. Among the techniques used, polyelectrolytic complexation (PC) and ionic gelation (IG) stands out due to convenience, speed, low cost, and possibility of using a versatile, biocompatible and natural polymer such as chitosan. Therefore, scoring and understanding the main factors that affect the stability of chitosan-based nanoparticles produced by PC and IG, and knowing the strategies that can be adopted to overcome these problems is extremely important. Thus, this review aims to provide an overview of anthocyanins and biopolymeric nanoparticles with an emphasis on PC and IG techniques. The main challenges that need to be faced when anthocyanins are incorporated into these nanoparticles will be scored, mainly when chitosan is used as a polymeric base. Also, some directions will be given to those who intend to develop new projects focusing on the stabilization of anthocyanins.